2023
DOI: 10.1101/2023.01.03.522496
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A dynamic partitioning mechanism polarizes membrane protein distribution

Abstract: The plasma membrane is widely regarded as the hub of the signal transduction network activities that drives numerous physiological responses, including cell polarity and migration. Yet, the symmetry breaking process in the membrane, that leads to dynamic compartmentalization of different proteins, remains poorly understood. Using multimodal live-cell imaging, here we first show that multiple endogenous and synthetic lipid-anchored proteins, despite maintaining stable tight association with the inner leaflet of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 107 publications
1
19
0
Order By: Relevance
“…Lower fluidity in regions with high cortical density may slow the diffusion of signaling activators, locally lowering excitability. Supporting this, multiple studies have reported lower membrane fluidity in back regions where actomyosin density should be high 6163 . Another possibility is related to the finding that anionic lipids such as PI(4,5)P2 on the inner leaflet of the membrane inhibits Ras/PI3K signaling 6 .…”
Section: Discussionmentioning
confidence: 64%
“…Lower fluidity in regions with high cortical density may slow the diffusion of signaling activators, locally lowering excitability. Supporting this, multiple studies have reported lower membrane fluidity in back regions where actomyosin density should be high 6163 . Another possibility is related to the finding that anionic lipids such as PI(4,5)P2 on the inner leaflet of the membrane inhibits Ras/PI3K signaling 6 .…”
Section: Discussionmentioning
confidence: 64%
“…Dictyostelium stable cell lines were generated by electroporation ( Li et al, 2021 ; Banerjee et al, 2022 ; Banerjee et al, 2023 ; Pal et al, 2023 ). Briefly, 1 × 10 7 cells were harvested, washed twice, and resuspended in 100 μL ice-cold H-50 buffer.…”
Section: Methodsmentioning
confidence: 99%
“…For imaging mammalian cells, both microscopes contained a temperature-controlled chamber held at 37°C and 5% CO 2 . Zeiss 800 or 780 was operated by ZEN Blue or Black software, respectively ( Kuhn et al, 2021 ; Banerjee et al, 2022 ; Banerjee et al, 2023 ; Pal et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Medium along with unadhered cells was removed and 450 μL fresh supplemented SB was gently added to the well. Cells were allowed to recover for 1 hr before imaging 35,36 .…”
Section: Methodsmentioning
confidence: 99%